Upaya Keluarga Pra-Sejahtera dalam Mempertahankan Keharmonisan Keluarga Pada Masa Pandemi Covid-19 Perspektif Hukum Keluarga Islam - Rusmala Dewi; Nurmala HAK; Vera Yuliana (CV. Doki Course and Training, 2023)
This article aims to examine pre-prosperous families who are still able to maintain harmony in the household even though they are affected by the pandemic. As it is known that the Covid-19 Pandemic has caused most family economies to be unfavorable, so that it has become a problem in maintaining household harmony and integrity. Thus, this research discusses the efforts of pre-prosperous families in maintaining family harmony during the Covid-19 pandemic and examines it from the perspective of Islamic family law. The type of research used is field research. The research location is in Suka Mulya Village, Lempuing District, Ogan Komering Ilir Regency. Primary data was obtained from interviews and observations, while secondary data was obtained from the literature concerned with the research object. The results of the study found that the efforts made by pre-prosperous families in maintaining family harmony even though they were affected by a pandemic were in accordance with the provisions stipulated in Islamic family law, namely getting closer to Allah, trying hard to fulfill their daily needs, doing things that positive, maintain communication between families and spend time with family.